CULTURAL DUALITY AND THE SEARCH FOR AUTHENTIC IDENTITY: ANALYZING BILLY BISWAS’ INNER CONFLICT IN ARUN JOSHI’S THE STRANGE CASE OF BILLY BISWAS - Singh, Rashmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper investigates the theme of cultural duality and the quest for authentic identity as portrayed in Arun Joshi’s The Strange Case of Billy Biswas. The protagonist, Billy Biswas, is caught between the inherited Westernized education of an urban elite and an innate pull toward a tribal, primordial way of life. By drawing on critical perspectives from postcolonial theory, existential philosophy, and recent debates on hybrid subjectivity, the study reinterprets Billy’s psychological and cultural conflict. It examines his estrangement from materialistic society, his gradual withdrawal into tribal life, and his ultimate pursuit of self-discovery as a symbolic critique of modernity. In doing so, the paper reveals how Joshi’s narrative not only explores cultural displacement but also anticipates contemporary concerns over identity and authenticity in a globalized world.